If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -2x + 7 = x + -15 Reorder the terms: 5 + 7 + -2x = x + -15 Combine like terms: 5 + 7 = 12 12 + -2x = x + -15 Reorder the terms: 12 + -2x = -15 + x Solving 12 + -2x = -15 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 12 + -2x + -1x = -15 + x + -1x Combine like terms: -2x + -1x = -3x 12 + -3x = -15 + x + -1x Combine like terms: x + -1x = 0 12 + -3x = -15 + 0 12 + -3x = -15 Add '-12' to each side of the equation. 12 + -12 + -3x = -15 + -12 Combine like terms: 12 + -12 = 0 0 + -3x = -15 + -12 -3x = -15 + -12 Combine like terms: -15 + -12 = -27 -3x = -27 Divide each side by '-3'. x = 9 Simplifying x = 9
| 4x+4*10=64 | | 2(q+5)-9q=94-q | | 2(x-5)=2x-7x-7 | | 3.25x-130=3x-115 | | -6+18y=36 | | -63x^2-17x+20= | | -8(2t+5)=8 | | 5x+4(-3x+16)=99 | | -3x^2-9x+30= | | 4v-36=5v | | -5(x-1)=6 | | q-5=0 | | 5+8Xn=29 | | (6)72=216 | | 2+1x+-6=7+-6 | | 4(f-4)=-32 | | 3p-1(6p+24)=0 | | -7h-19=2h+17 | | X^3+3x^2+x= | | 3(m+12)+20=5 | | (6)3=216 | | 9n=7n+49 | | 40=x+35 | | 9e^2=66.5 | | -10(s+5)=-53 | | -4n-8=4(-3n+2) | | 9e^1=16 | | 25x-(8)=22x+10 | | 4x(5x+1)=5x+1 | | 2x=x-(8) | | 8r-7=2r+35 | | 16x+8x=10 |